URGENSI PENGEMBANGAN KARAKTER MANDIRI DALAM MENGEMBANGKAN KECERDASAN MORAL MELALUI PEMBELAJARAN DARING - Muhammad Kholil; Muhammad Mushfi El Iq Bali; Siti Fatimah (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
Abstract: Sophisticated information technology can have a great influence on the shape of human life, especially through information and the use of the internet which is free and without limits. The process of forming character education in the school environment really helps students in matters of responsibility through ethical development and the process of training character well through universal values. This type of research is using a descriptive qualitative research approach. This study collects data in the form of data in the form of sentences or describes from the subject carried out by interview. The subjects consisted of Islamic Religious Education teachers at MAN 2 Probolinggo. The data from this study are the results of interviews with subjects who describe the urgency of developing independent character in developing moral intelligence through online learning. The teacher's efforts in the process of teaching and learning activities always review those related to values, morals and attitudes with simple events, reminding them to have tolerance, fairness, empathy, and increasing respect for teachers or for older people and events that concerned with morals.